2015
DOI: 10.17576/jem-2015-4902-10
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Migrasi Masuk dengan Faktor-Faktor Penarik : Kajian Kes di Malaysia

Abstract: In and out migration to the destination areas is the main factor contributing to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This is because; the population in Kuala Lumpur came from various people from other states in Malaysia. History showed that Kuala Lumpur has a diversified population since 1980s which resulted from the internal migration during that time; and the number still increased in 2000s (Hussain et al, 2015;Mishra, 2018). A high number of internal migrants (from other states such as Kedah, Penang, Kelantan, Terengganu, Sabah and Sarawak) to Kuala Lumpur have changed the landscape of its population distribution.…”
Section: Methodsmentioning
confidence: 99%
“…This is because; the population in Kuala Lumpur came from various people from other states in Malaysia. History showed that Kuala Lumpur has a diversified population since 1980s which resulted from the internal migration during that time; and the number still increased in 2000s (Hussain et al, 2015;Mishra, 2018). A high number of internal migrants (from other states such as Kedah, Penang, Kelantan, Terengganu, Sabah and Sarawak) to Kuala Lumpur have changed the landscape of its population distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The four main offer factors identified include social, economic, urban, and personal infrastructure and services offered. According to Hussain, Abdullah & Abdullah (2015), migration occurs when people begin to look for opportunities to change their life for the better in the city. The possible source of income in the countryside can be limited compared to big cities.…”
Section: Sub-theme 4c: Being Away From Familymentioning
confidence: 99%
“…Some studies have been conducted to view the relationship of migration and investments (Hussain et al 2015;Foad 2011;Xue & Gao 2012). In Malaysia, Hussain et al (2015) found that there is a long-run relationship between in-migration with FDI in Kuala Lumpur and the long-run relationship between in-migration and domestic investment in Penang. In China, Xue and Gao (2012) found that most people in rural areas to migrate to urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%